2012
DOI: 10.1590/s0100-55022012000500017
|View full text |Cite
|
Sign up to set email alerts
|

Trabalho em saúde e trabalho médico: especificidades e convergências

Abstract: Este ensaio apresenta um contraponto entre o trabalho em saúde e o trabalho médico a partir das relações existentes entre o conhecimento e a prática. Assume que a problemática da saúde diz respeito às relações entre a natureza e a cultura. Reconhece que a introdução das ciências humanas no campo da saúde relativizou o discurso biológico e que a marca desse campo é a multidisciplinaridade. Identifica o estilo de pensamento biomédico como o principal responsável pelas especificidades do agir médico. Analisa e cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The "Roles, reality and idealization of working in the FHS" category is demonstrated in Table 2, which revealed the work focused on preventing the users' complications and diseases, bringing to light the reality the Atlas.ti software, version 8.0, and anchored on the theoretical look of the authors that promote reflections about the work 11,12 and work process in health 2,[13][14][15][16] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The "Roles, reality and idealization of working in the FHS" category is demonstrated in Table 2, which revealed the work focused on preventing the users' complications and diseases, bringing to light the reality the Atlas.ti software, version 8.0, and anchored on the theoretical look of the authors that promote reflections about the work 11,12 and work process in health 2,[13][14][15][16] .…”
Section: Methodsmentioning
confidence: 99%
“…The participants demonstrated that there are fragilities based on the short-termist biomedical model (hegemonic model). The health actions taken in a biomedical approach, anchored on a curative culture, reflect user's practices also based on such perspective 13 . The excerpt from the following interview illustrates such a statement.…”
Section: Challenges and Perspectives Of Working In The Fhsmentioning
confidence: 99%